Surveying adjustment datum and relative deformation accuracy analysis - Chen, Guoliang; Meng, Xiaolin; Yao, Lianbi (Taylor & Francis, 2014)
In the surveying adjustment, unknown parameters are usually not direct observations, but the elements related to these direct observations. In order to determine the unknown parameters adequate known data should be provided, and these necessarily required known data are used to form the adjustment datum. Under different datums, different results will be obtained even with the same direct observations. However, in the practical adjustment calculation, the datum and its effect on the results are always ignored. In this paper, the adjustment datum is firstly discussed and defined as datum equations. Then an adjustment method based on the datum equations and least squares is presented. This method is a generic one, not only suited for the case in an ordinary datum but also in the gravity centre datum or a quasi-datum, and can be easily used to analyse different deformations. Based on this method, the transformation between different reference frames is derived. It shows that the calculation results, deformation and positioning accuracy under one kind of datum are relative and generic. A case study is further introduced and used to test this new method. Based on the case study, the conclusions are reached. It is found that the relative positional root mean square error of each point becomes bigger as the distance between the point and the datum increases, and the relative deformation offsets under different kinds of datum are helpful for reliable deformation analysis.